Adobe Photoshop Lightroom 4 learn by video - Aaland, Mikkel (Peachpit Press, 2012)
"This complete training program from Adobe Press and video2brain combines over 10 hours of exceptional video training to teach you the fundamentals of Adobe Lightroom 4 as well as the basic principles of image processing and management. Award-winning photographer and teacher Mikkel Aaland walks you through the main features of the program, showing you how to import images, apply keywords, and create collections; then moving on to the develop module, where you use sophisticated controls to bring out the best in each image. Mikkel also shows you how to export your photos to print, the web, or to other media. The course includes extensive coverage of what's new in Lightroom 4 such as the map and book modules, and vastly improved image processing engine."--Resource description page.
Title from resource description page (viewed Sept. 26, 2012). - Footer on screen: Video2brain
Keywords: Adobe Photoshop lightroom; Photography -- Digital techniques; Photographie numérique; Photography; Digital techniques; Electronic videos